Color coherence in multi-jet final states - Hautmann, F; Jung, H (2009)
We discuss coherent QCD radiation from space-like parton branching and its effects on multi-jet final states at high-energy hadron colliders. Coherence effects for small longitudinal momentum fractions x are not included in the branching algorithms of standard shower Monte Carlo event generators. On the other hand, they are taken into account only partially in perturbative next-to-leading-order calculations for multi-jets. Such effects are present to all orders in α s and can become logarithmically enhanced with sqrt(s) / E T, where E T is the hardest jet transverse energy. We present results of summing coherence effects to all orders by parton-branching Monte Carlo methods based on transverse-momentum dependent matrix elements. © 2008 Elsevier B.V. All rights reserved.